Study on the operating characteristics of a compound automatic transfer switch based on forced current commutation. Issue 16 (14th January 2019) - Lu, Qu; Zhanqing, Yu; Tianyu, Wei; Zhengyu, Chen; Bin, Liu; Rong, Zeng
Abstract : The automatic transfer switch can solve the problem of voltage drop and instantaneous power interruption, which is one of the most reliable and economical ways to improve the reliability and quality of the power supply. In view of the application demand of the important electric field, this paper puts forward the technology scheme of a compound automatic transfer switch based on forced current commutation, which is characterised by high reliability, fast switching and active and passive combined protection. First, the general technical scheme and working principle of the compound automatic transfer switch are introduced. Then, the simulation model of power distribution system with one master and one standby automatic transfer switch is established, and the system simulation is carried out to analyse the influence of the fault type on switching effect. Finally, the feasibility of the compound automatic transfer switch is verified by experiments, and its operational characteristics are obtained. It provides theoretical and technical basis for the product development and engineering application of the compound automatic transfer switch.